Impact Assessment of the Convergence of IFRS and US. GAAP on the Quality of Financial Reporting- A Comparative Study - Djoudi, Imane; Gasmi, Said (Journal of Research in Finance and Accounting, 2021)
The objective of this research is to examine and evaluate the results of Convergence project that began in 2002 to remove the differences between the International Financial Reporting Standards (IFRS) and United States Generally Accepted Accounting Principles (US. GAAP). Our paper is considered a comparative analytical study, and it is motivated by the ongoing harmonization process in accounting standard setting and recent convergence projects by the FASB and the IASB. First, we give an overview about the progress of the convergence, and then we study the most important results reached during this project. Finally, the difficulties and the most important criticisms will be discussed. The paper concluded that the convergence between IFRS and US. GAAP is one of the most efficient methods adopted to achieve the goal of high-quality international accounting standards but it is a short-term solution and there are more effective ways that must be found to achieve the stated goal.